Geothermal In-Situ Heat Transfer Control Factor Simulation and Numerical Analysis - Sun, Hao; Tai, Dezhi (International Journal of Natural Resources and Environmental Studies, 2024)
Geothermal energy, as a renewable and clean energy source, holds immense potential in meeting energy demands and reducing carbon emissions. Its unique sustainability and environmental friendliness make it an important complement to addressing today's energy challenges. Coaxial tubing in-situ heat exchange technology for geothermal wells, as a key extraction method for geothermal energy, is subject to control by multiple critical factors that directly relate to its efficiency and feasibility. This paper aims to delve into the technology of coaxial tubing in-situ heat exchange for geothermal wells through numerical simulation analysis, with a focus on studying the impacts of three key factors on its performance: heat transfer medium flow rate, inlet water temperature, and cement thermal conductivity. Through numerical analysis, this study aims to reveal the variations of these factors to provide more refined control methods and optimize the coaxial tubing in-situ heat exchange technology for geothermal wells. By conducting experimental simulations and numerical analysis on these key factors, this paper aims to provide strong support for optimizing the coaxial tubing in-situ heat exchange technology for geothermal wells, which will contribute to advancing geothermal energy technology and promoting the sustainable utilization of clean energy.